UPAYA PENGEMBANGAN KOMPETENSI PROFESIONAL GURU SMK DALAM MENINGKATKAN KINERJA PEMELAJARAN - Supriyati, Tati (2013)
As a holding professional position, teacher is qualified to actualize and to develop the professional competence. Without constituted by adequate professional competence, it is the little possibility to all teachers to come up the professional in executing its duty. Therefore, actualization and professional competence development will become the important part in education management. Through this research various professional interest development efforts in improving its performance will be learnt. This research is executed on SMK Negeri 1 Subang. The research method that is used is a quantitative descriptive method with the correlation approach. Quantitative method applied by measuring teacher perception to professional competence improvement and the study performance realized through actualization professional competence of the teacher. Quantitative data is obtained through questionnaire and analyzed using the descriptive statistical approach and also correlation coefficient calculation. Sample becoming target in this research are 27 the teachers of SMK Negeri 1 Subang. Teacher's professional competence development is stud'ed by expressing such aspects are : (1) education and training, (2) performance management, (3) career development, (4) discipline and spirit job development, and (5) prosperity improvement. According to the result of data analyses found that the more positive of teacher perception to professional competence development effort, the higher study performance of the teacher will be. In other words, study performance as professional competence actualization can be increased by improving professional competence development effort of the teacher. Professional competence development of the teacher of SMK Negeri 1 Subang can be executed through the following stages ; (1) providing the education and training program appropriates with the teacher's need in executing its duty; (2) performance management based on objective assessment of teacher achievement; (3) career development bases on the teacher's ability in executing the duty; (4) discipline construction and job spirit so that the teacher can work better and shows good result of job; and also (5) prosperity improvement which can be conducted by optimizing the existing source of fund both to increase earnings and to support to its professional competence development as well.